2022
DOI: 10.3389/fpubh.2022.887069
|View full text |Cite
|
Sign up to set email alerts
|

Different Impacts of COVID-19 on Quality of Therapy, Psychological Condition, and Work Life Among Occupational Therapists in Physical and Mental Health Fields

Abstract: BackgroundThe negative impacts of the coronavirus disease 2019 (COVID-19) pandemic have worsened the quality of therapy, psychological condition, and work life of second-line healthcare workers and occupational therapists (OTs). However, no study has investigated whether the impact of COVID-19 varies among OTs working in different fields. This study aimed to investigate the differences on the impact of COVID-19 between OTs in the physical and mental health fields.MethodsA cross-sectional online survey was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Information provision from the workplace also has a critical role in addressing mental health conditions. A recent report suggested that sufficient information from the workplace significantly reduced the risk of mental health problems ( 6 , 21 ), and this finding is consistent with previous evidence that showed the effectiveness of information provision for mental support during previous infectious outbreaks such as H1N1 and SARS ( 22 24 ). Other recent reports suggested that social connectedness was associated with a lower level of perceived stress and COVID-19-related burnout ( 1 , 25 ).…”
Section: Introductionsupporting
confidence: 85%
“…Information provision from the workplace also has a critical role in addressing mental health conditions. A recent report suggested that sufficient information from the workplace significantly reduced the risk of mental health problems ( 6 , 21 ), and this finding is consistent with previous evidence that showed the effectiveness of information provision for mental support during previous infectious outbreaks such as H1N1 and SARS ( 22 24 ). Other recent reports suggested that social connectedness was associated with a lower level of perceived stress and COVID-19-related burnout ( 1 , 25 ).…”
Section: Introductionsupporting
confidence: 85%
“…Workers in these categories experienced lower levels of mental health compared to their counterparts. Sawamura, Ito, Miyaguchi, Nakamura, and Ishioka (2022) found that mental health workers exhibited a significant decline in mental health quality and an increase in workload. Multinomial logistic regression analysis revealed associations between changes in mental health quality and depression and insomnia.…”
Section: Literature Reviewmentioning
confidence: 99%